AGAMA SARKAWI (Studi kasus di Desa Siasem Kabupaten Brebes Jawa Tengah) - Subkhan Ridlo (Analisa: Journal of Social Science and Religion, 2008)
This case study aims to describe and to analyze SarkawiReligion at Padukuhan Limbungan, Siasem Village, Brebes Regency.All Sarkawi followers are Islam; however their neighborhoodcommunity called them Sarkawi followers, why? It is because theyhave different faith, which is faith in forbidden to eat goat meat andpenance for those being death. Forbidden of eating goat meat caused by belief that come upfrom the story told by Sarkawi and penance is performed by ritualat the center (house of Sarkawi leader). By the ritual, spirit of thedeaths will be admitted by the almighty.